36th AIAA Aerospace Sciences Meeting and Exhibit 1998
DOI: 10.2514/6.1998-905
|View full text |Cite
|
Sign up to set email alerts
|

HSCT configuration design using response surface approximations of supersonic Euler aerodynamics

Abstract: A method has been developed to efficiently implement supersonic aerodynamic predictions from Euler solutions into a highly constrained, multidisciplinary design optimization of a High-Speed Civil Transport (HSCT) configuration. The method alleviates the large computational burden associated with performing CFD analyses and eliminates the numerical noise present in the analyses through the use of response surface (RS) methodologies, a variation of the variable-complexity modeling (VCM) technique, and coarse gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In addition to other research conducted with higher fidelity aerodynamic RS models [24], work has been done on structural RS models for a HSCT configuration optimization over a small design box [25]. Work is currently in progress to use the RSM presented to construct structural RS models for the large design box used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to other research conducted with higher fidelity aerodynamic RS models [24], work has been done on structural RS models for a HSCT configuration optimization over a small design box [25]. Work is currently in progress to use the RSM presented to construct structural RS models for the large design box used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal design variable values and weights are given in Tables 3 and 4. Further details of these cases are presented by Knill et al 33 Because of computational expense, the full quadratic Euler RS models are not created for the 20-variable design. This is exactly the situation for which the reduced-term incremental RS models were developed.…”
Section: Optimization Resultsmentioning
confidence: 98%
“…Second order correction methods that require second derivatives of the high-and low fidelity response were introduced by Eldred et al 92 implemented in the DAKOTA software 63 and compared to other metamodeling techniques. 93 Knill et al 94 stated that the gradient-based low fidelity model correction procedure was effective in reducing the computational cost but it was adversely affected by the presence of numerical noise in aerodynamic and structural response values. To circumvent this, Giunta et al 95 suggested to initially perform a thorough design space exploration utilizing a low fidelity model, and identify and exclude "non-sense" regions arriving at a much reduced ribbon-like domain in the design space.…”
Section: Multi-level and Multi-fidelity Approximationsmentioning
confidence: 99%